GO and CNT template impact on the WO3/Bi2S3 photocatalytic activity for pharmaceutical active compounds removal - Enesca, Alexandru (Journal of Photochemistry & Photobiology, A: Chemistry, 2025)
A combined sol–gel and doctor blade techniques were used to obtain two types of composites. Graphene oxide (GO) and carbon nanotubes (CNTs) were used as template in the sol–gel procedure which include two steps: WO3 and Bi2S3 development. The composites crystallinity and morphology were investigated indicating the formation of monoclinic WO3 and orthorhombic Bi2S3. The GO template samples exhibit porous sponge-like morphology with 285 m2/g SBET, while the CNTs template samples have a granular morphology with 294 m2/g SBET. The elemental analysis indicate that the composite components are evenly distributed through the sample. Both GO and CNTs based samples have a predominant polar component of the surface energy which make them suitable candidate for applications in aqueous environments. The photocatalytic removal efficiency was tested in the presence penicillin G and amoxicillin (150 ppm) under UV and Vis irradiation. The highest efficiencies corre spond to GO/WO3/Bi2S3 which was able to remove 57.43 % PEN-G and 63.94 % AMO. The photocatalytic mechanism was investigated and described in details.
Keywords: Antibiotics; Carbon nanotubes; Graphene oxide; Photocatalysis; Wastewater